Cardiac cell proliferation is not necessary for exercise‐induced cardiac growth but required for its protection against ischaemia/reperfusion injury. Issue 8 (17th March 2017) - Bei, Yihua; Fu, Siyi; Chen, Xiangming; Chen, Mei; Zhou, Qiulian; Yu, Pujiao; Yao, Jianhua; Wang, Hongbao; Che, Lin; Xu, Jiahong; Xiao, Junjie
Abstract: The adult heart retains a limited ability to regenerate in response to injury. Although exercise can reduce cardiac ischaemia/reperfusion (I/R) injury, the relative contribution of cardiac cell proliferation including newly formed cardiomyocytes remains unclear. A 4‐week swimming murine model was utilized to induce cardiac physiological growth. Simultaneously, the antineoplastic agent 5‐fluorouracil (5‐FU), which acts during the S phase of the cell cycle, was given to mice via intraperitoneal injections. Using EdU and Ki‐67 immunolabelling, we showed that exercise‐induced cardiac cell proliferation was blunted by 5‐FU. In addition, the growth of heart in size and weight upon exercise was unaltered, probably due to the fact that exercise‐induced cardiomyocyte hypertrophy was not influenced by 5‐FU as demonstrated by wheat germ agglutinin staining. Meanwhile, the markers for pathological hypertrophy, including ANP and BNP, were not changed by either exercise or 5‐FU, indicating that physiological growth still developed in the presence of 5‐FU. Furthermore, we showed that CITED4, a key regulator for cardiomyocyte proliferation, was blocked by 5‐FU. Meanwhile, C/EBPβ, a transcription factor responsible for both cellular proliferation and hypertrophy, was not altered by treatment with 5‐FU. Importantly, the effects of exercise in reducing cardiac I/R injury could be abolished when cardiac cell proliferation was attenuated in mice treated with 5‐FU. In conclusion, cardiac cell proliferation is not necessary for exercise‐induced cardiac physiological growth, but it is required for exercise‐associated protection against I/R injury.